Collaborative Framework Arrangement for Agile/Leagile Procurement and Supply of Humanitarian Food Aid: A Case Study of Malaysia - Ponnusamy, Perumal (Curtin University, 2019)
Drawing from complimentary perspective of supply chain management’s (SCM) prevailing theories i.e. transactional cost analysis, social exchange theory and contingency variables as constructs; and its principles of lean, agile and leagile as non-financial performance indicator; this study examines collaborative framework arrangements (FAs) as procurement tool with small and local suppliers for the supply of food-aid by governmental based humanitarian relief organizations for flood in Malaysia. The study established linkages between collaborative FAs to agile/leagile practices.